SIMULATION NETLIST GENERATOR, SIMULATION NETLIST GENERATION METHOD, AND COMPUTER PROGRAM - ITO SOICHI; YAJIMA EIJI; KANEKO TOSHIKO (2012)
PROBLEM TO BE SOLVED: To reduce a simulation time related to a power supply control in a circuit.SOLUTION: A search start component is specified based on "component information 110, terminal information 120, and inter-terminal connection information 100" of components constituting a circuit. A power supply terminal and a reset terminal of the search start component and a control network name of the power supply circuit are defined as search start points. Input/output network names of the power supply circuit, a power supply network name, a ground network name, and a search end component specified based on the component information 110 are defined as search end points. Components from the search start point to the search end point are searched, and the connection information of the components is specified, to generate a simulation netlist of components in the search route.